(untitled) (Conference Zone, 2022)
The article deals with the aggravation of global, geopolitical, ethnic, national problems in the context of the integration processes of globalization. The growth of national identity has become today the most important issue as a means of protection against this very situation. National identity is the basis of the legitimacy of nation-states, it forms and strengthens the idea of citizens about the unity of historical destiny, and as long as there is a sense of the unity of the nation and cultural identity, there is a nation.